Assessment of Genetical, Pre, Peri and Post Natal Risk Factors of Deciduous Molar Hypomineralization (DMH), Hypomineralized Second Primary Molar (HSPM) and Molar Incisor Hypomineralization (MIH): A Narrative Review - Andrea Butera; Carolina Maiorani; Annalaura Morandini; Manuela Simonini; Stefania Morittu; Stefania Barbieri; Ambra Bruni; Antonia Sinesi; Maria Ricci; Julia Trombini; Elisa Aina; Daniela Piloni; et al. (MDPI AG, 2021)
Objectives: Analyze defects in the state of maturation of the enamel result in an adequate volume of enamel, but in an insufficient mineralization, which can affect both deciduous teeth and permanent teeth. Among the most common defects, we recognize Deciduous Molar Hypominerlization (DMH), Hypomineralized Second Primary Molar (HSPM), and Molar Incisor Hypomineralization (MIH). These, in fact, affect the first deciduous molars, the second deciduous molars and molars, and permanent incisors, respectively, but their etiology remains unclear. The objective of the paper is to review studies that focus on investigating possible associations between genetic factors or prenatal, perinatal, and postnatal causes and these enamel defects. Materials and methods: A comprehensive and bibliometric search for publications until January 2021 was conducted. The research question was formulated following the Population, Intervention, Comparison, Outcome strategy. Case-control, cross-sectional, cohort studies, and clinical trials investigating genetic and environmental etiological factors of enamel defects were included. Results: Twenty-five articles are included. For genetic factors, there is a statistical relevance for SNPs expressed in the secretion or maturation stage of amelogenesis (16% of studies and 80% of studies that investigated these factors). For prenatal, perinatal, and postnatal causes, there is a statistical relevance for postnatal factors, such as the breastfeeding period (2%), asthma (16%), high fever episodes (20%), infections/illnesses (20%), chickenpox (12%), antibiotic intake (8%), diarrhea (4%), and pneumonia (4%). Conclusions: The results are in agreement with the multifactorial idea of the dental enamel defects etiology, but to prove this, further studies enrolling larger, well-diagnosed, and different ethnic populations are necessary to expand the investigation of the genetic and environmental factors that might influence the occurrence of DMH, HPSM, and MIH.